Efektivitas Program Inaportnet Dalam Pelayanan Penerbitan Surat Pemberitahuan Kedatangan Kapal (Pkk) di Kantor Otoritas Pelabuhan Utama Tanjung Perak Kota Surabaya - Syafira Dyah Anggaraini; Lunariana Lubis (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2022)
The increase of ship services every year needs implementation at the Port effectively. The purpose of this study was to describe and analyze the effectiveness and supporting and inhibiting factors of the Inaportnet program (online service for issuing Ship Arrival Notifications) at the Tanjung Perak Main Port Authority, Surabaya. This study uses a qualitative method with a case study approach. Data collection techniques were carried out through observation, interviews, and documentation. The theory used is a modification of the theory from Budiani and Sutrisno which said there are 6 aspects, namely Program Understanding, Target Accuracy, Timeliness, Goal Achievement, Program Monitoring, and Real Change. The results of the study showed that the effectiveness of the Inaportnet program has been running effectively. However, one aspect was found, namely the Program Understanding Level that had not run optimally. The supporting factor for the program is the ability of competent Human Resources to complete their duties. However, the service continues to run manually. This study recommends increasing the explanation of information about the program through video tutorials that are uploaded on social media.